The Acme Realization of Medical Nurses: Autobiographical Markers of Psychological Defense Strategies - Mykhal’ska, Yulia (Psychological Prospects Journal, 2014)
The article presents the results of the theoretical and empirical research of autobiographical manifestation of the medical nurses’ psychological defense strategies based on the ties between treating process and communicative and personality features. The autobiographical content of the nurse’s psychological defense is viewed as a marker of her deontological competence and culture. The results of the empirical study with the application of the factor analysis and statistical methods allowed defining a set psychological fact. First, the nurses’ emotional tension degree determines the variety of their defense strategies. Secondly, the defense strategies of nurses who work in polyclinics contain substitution, rejection, and projection. By contrast, those who work in the clinic departments of infectious diseases apply compensation and rationalization strategies. Under stress, the latter illustrate more sensitivity, empathy, patience, social direction, and dependence, whereas the former demonstrate less sensitivity, empathy, and altruistic friendly behavior. Next, the research findings based on the autobiographical method prove the fact that nurses with over seven-year seniority in the departments of infectious diseases, in contrast to those who work in policlinics, show higher indices of acme-realization, which defines their degree of communicative and deontological competence and professional maturity.